PERFORMANCE TESTING OF THE â€œMAXXI CORN TYPE-G AUTOMATICâ€ COMBINE HARVESTER MACHINE FOR RICE RICE HARVESTING WITH TWO DIFFERENT TRANSMISSIONS IN TABABO VILLAGE, BELANG DISTRICT SOUTHEAST MINAHASA DISTRICT - F. S. Ekel; L. C. CH. E. Lengkey; D. P. M. Ludong (Universitas Sam Ratulangi, 2023)
ABSTRACT The purpose of the study was to test the performance of the Maxxi corn type-G automatic Combine harvester machine used to harvest lowland rice with two different transmissions which include, harvesting process, harvesting capacity and threshing capacity. The study was conducted in May 2020, in Tababo Village, Belang District, Southeast Minahasa Regency, North Sulawesi on the land of the Southeast Minahasa Agricultural Seed Center. The research method used is the experimental method, then the data obtained are presented in tabular form, and processed descriptively. The results showed that the theoretical field capacity and effective field capacity in gear 2 transmission were relatively larger than in gear 1 transmission and field efficiency in gear 1 transmission was relatively larger than field efficiency in gear 2 transmission bigger, that is 631.603 kg/hour compared to gear 1 transmission which is 432.54 kg/hour. The performance of the combine harvester machine is strongly influenced by the condition of the land at the time of harvesting, greatly affecting the movement and transmission of tools during harvesting. The time needed to harvest the rice is shorter. Combine harvester machine working capacity reaches 5 hours per hectare. The performance of the Maxxi corn combine harvester type-Gs automatic is strongly influenced by land area, land conditions, operator expertise and is also strongly influenced by gear 1 transmission and gear 2 transmission.